The diet of itinerant male Hooker's sea lions, Phocarctos hookeri, at sub-Antarctic Macquarie Island - McMahon, CR; Hooley, D; Robinson, S (1999)
Scats were collected from itinerant male Hooker's sea lions, Phocarctos hookeri, at Macquarie Island and the uneroded faunal remains used to assess the diet. Uneroded sagittal otoliths were used to identify teleost fish and to calculate fish size. Prey items included 14 taxa of teleost fish, cephalopods, gastropods, crustaceans and fur seals. Fish constituted the primary component of the diet. Prey species previously uncommon in the diet of seals and penguins around Macquarie Island were commonly eaten by Hooker's sea lions. The sub-Antarctic horse fish (Zanclorhynchus spinifer) and the Patagonian tooth fish (Dissostichus eleginoides) were the two most abundant species and occurred in 62.5% and 41.7% of all scats respectively. There were no age-specific and individual differences in the diet of sea lions. Seasonal variances in diet were absent. Small plastic fragments (diameter ~1 mm) were found only in association with otoliths of Electrona subaspera. Some overlap was seen between the diet of itinerant male Hooker's sea lions and the commercial fisheries that currently operate around Macquarie Island.